1997
DOI: 10.1099/0022-1317-78-6-1507
|View full text |Cite
|
Sign up to set email alerts
|

Baculovirus transactivator IE1 is functional in mammalian cells.

Abstract: IE1 of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…These results highlight the cell dependence of AAD gene activation and the promiscuous nature of the AcMNPV IE1 AAD. Previous studies have shown that the native AcMNPV IE1 is able to activate gene expression in mammalian BHK-21 cells (Carbonell et al, 1985;Carbonell & Miller, 1987;Murges et al, 1997). Our results indicate that this is due, at least in part, to the AAD domain of IE1, which appears to be a more universal activation domain, similar to VP16 AAD.…”
Section: Discussionsupporting
confidence: 59%
“…These results highlight the cell dependence of AAD gene activation and the promiscuous nature of the AcMNPV IE1 AAD. Previous studies have shown that the native AcMNPV IE1 is able to activate gene expression in mammalian BHK-21 cells (Carbonell et al, 1985;Carbonell & Miller, 1987;Murges et al, 1997). Our results indicate that this is due, at least in part, to the AAD domain of IE1, which appears to be a more universal activation domain, similar to VP16 AAD.…”
Section: Discussionsupporting
confidence: 59%
“…The most successful use of baculovirus for delivery and expression of genes in mammalian cells used a CMV promoter and transduction at 37OC (10)(11)(12)(13)(14)(15)(16)(17). We found that transduction of primary pancreatic dissociated islet cells and other cell lines using baculovirus at 37OC was four-to fivefold higher than that at room temperature (L.M., L.H.P., unpublished data).…”
Section: Discussionmentioning
confidence: 98%
“…Recently, it was shown that baculovirus can be transported into some primary cells and into many cell lines derived from mouse, rat, porcine, and human tissues (10)(11)(12)(13)(14)(15)(16)(17). Using mammalian promoters, baculovirus enabled efficient transient expression of reporter genes in mammalian cells (10)(11)(12)(13)(14)(15)(16)(17). Condreay et al (17) also reported stable baculovirus transduction of several mammalian cell types with expression of a reporter gene for multiple passages.…”
mentioning
confidence: 99%
“…The persistence of large regions of the viral genome in cells, which we have demonstrated in this report, raises the possibility that immediate early viral gene products could be expressed in mammalian cells that receive a virus. One of these gene products, the IE-1 transactivator, has been demonstrated to activate transcription from viral early promoters in mammalian cells (20).…”
Section: Discussionmentioning
confidence: 99%